Virulence factors are preserved within carbapenem-resistant Acinetobacter baumannii clades - Mor N. Lurie-Weinberger; Adi Cohen; Hadas Kon; Ophir Kastel; Alona Keren-Paz; David Schwartz; Jonathan Lellouche; Amir Nutman; Sammy Frenk; Vered Schechner; Elizabeth Temkin; Lena E. Friberg; et al. (Virulence)
Carbapenem-resistant Acinetobacter baumannii (CRAB) is an important threat to hospitalized patients. The virulence of A. baumannii varies between strains and geographic locations, which is believed to be related to its genetic plasticity. A comprehensive evaluation of virulence factor (VF) content of CRAB across genetically related clones is lacking. Therefore, we aimed to determine the evolution of VFs among 246 CRAB isolates belonging to major STs, ST2 and ST3. We used WGS to assess 136 VFs and found that 110 VFs were present in most isolates (49 VFs were universally present, 61 were ubiquitous) and 25 occurred sporadically. The distribution of the 25 sporadic VF genes was homogenous in ST3 but heterogeneous in ST2. Within ST2, we found high intra-clade homogeneity and high inter-clade heterogeneity of VFs. The homogeneity of VF content in ST2 clades and its uniformity in ST3 suggest a distant evolutionary segregation of VFs at the root of ST/clade divergence. VF content reflects remote events resulting in minimal variation between isolates belonging to the same ST/clade. Thus, the alleged differences in virulence of CRAB strains between geographical locations reflect differences in clonal distribution.